Traditional Chinese Medicine Qingre Huoxue Treatment vs. the Combination of Methotrexate and Hydroxychloroquine for Active Rheumatoid Arthritis: A Multicenter, Double-Blind, Randomized Controlled Trial - Gong, Xun; Liu, Wei-Xiang; Tang, Xiao-Po; Wang, Jian; Liu, Jian; Huang, Qing-Chun; Liu, Wei; Fang, Yong-Fei; He, Dong-Yi; Liu, Ying; Gao, Ming-Li; Wu, Qing-Jun; et al. (Frontiers in Pharmacology, 2021)
Traditional Chinese medicine (TCM) has been used successfully to treat rheumatoid arthritis (RA). Qingre Huoxue treatment (Qingre Huoxue decoction (QRHXD)/Qingre Huoxue external preparation (QRHXEP)) is a therapeutic scheme of TCM for RA. To date, there have been few studies comparing the efficacy and safety of QRHXD and conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) for the treatment of active RA. This was investigated in a multicenter, double-blind, randomized controlled trial involving 468 Chinese patients with active RA (disease activity score [DAS]-28 >3.2) treated with QRHXD/QRHXEP (TCM group), methotrexate plus hydroxychloroquine (Western medicine [WM] group), or both (integrative medicine [IM] group). Patients were followed up for 24 weeks. The primary outcome measure was the change in DAS-28 from baseline to 24 weeks. The secondary outcome measures were treatment response rate according to American College of Rheumatology 20%, 50%, and 70% improvement criteria (ACR-20/50/70) and the rate of treatment-related adverse events (TRAEs). The trial was registered at ClinicalTrials.gov (NCT02551575). DAS-28 decreased in all 3 groups after treatment (P<0.0001); the score was lowest in the TCM group (P<0.05), while no difference was observed between the WM and IM groups (P>0.05). At week 24, ACR-20 response was 73.04% with TCM, 80.17% with WM, and 73.95% with IM (based on the full analysis set [FAS], P>0.05); ACR-50 responses were 40.87%, 47.93%, and 51.26%, respectively (FAS, P>0.05); and ACR-70 responses were 20.87%, 22.31%, and 25.21%, respectively (FAS, P>0.05). Thus, treatment efficacy was similar across groups based on ACR criteria. On the other hand, the rate of TRAEs was significantly lower in the TCM group compared to the other groups (P<0.05). Thus, QRHXD/QRHXEP was effective in alleviating the symptoms of active RA—albeit to a lesser degree than csDMARDs—with fewer side effects. Importantly, combination with QRHXD enhanced the efficacy of csDMARDs. These results provide evidence that QRHXD can be used as an adjunct to csDMARDs for the management of RA, especially in patients who experience TRAEs with standard drugs.